The Uncertainty of Credit Safety. Issue 73 (September 2014) - Osband, Kent
<x xml:space="preserve">Abstract</x> It is inherently difficult to distinguish safe debts that won't default from risky debts that haven't defaulted yet. The extra uncertainty calls for additional capital buffers on highly rated debt.